Yuppies, Junkies, and Mules: narcotic subjectivities, dialectical images, and contemporary art in Córdoba (Argentina) - Blazquez, Gustavo (2011)
Any analysis of contemporary societies lacks objectivity if it omits the production, distribution, and consumption on a planetary scale of psychoactive substances considered illegal by nation states and international organizations. In the management of these "illegal molecules" dissolved in the humors that constitute the inner space of subjects, a “war machine” has been installed that is capable of "exciting" both life and death. What subjectivities might such an active narco-machine produce in the capitalism of the first decade of the 21st century? This matter is considered through an ethnography of the nightly consumption habits of youths in the city of Córdoba and their experiences of cocaine use. As a counterpoint, the essay then examines the work of the Argentinean artist Adriana Bustos as she critically explores the relationship between colonial biomules and contemporary narcomules.